TAKING FORWARD THE FEMINIST AND CRITICAL PROJECT ON THE POLITICS OF REPRODUCTION - Shefer, Tamara (PINS-Psychology in Society, 2025)
Macleod, Catriona (2011) “Adolescence”, pregnancy and abortion: Constructing a threat of degeneration. London & New York: Routledge. ISBN 978-0-415-55338-4 pbk. Pages 184. “Teenage pregnancy” and parenting together with abortion remain stigmatized in South Africa and are controversial topics globally. Recent headlines of newspapers reporting on teenage pregnancy are testimony to the emotive and moralistic discourse that the image of a pregnant schoolgirl continues to inspire in the local public imagination. Consider for example the image of disaster and despair encapsulated in a national newspaper’s loud title “Pregnancy tsunami” in an article on the pregnancy at local schools (The Times, 21 February 2011 - front page). Well-known critical and feminist psychologist, Catriona Macleod has for many years been invested in unpacking these dominant discourses – not only in the public domain but more importantly among scholars and policy-makers in this terrain – to expose the way in which apparently evidence-based and learned responses to teenage pregnancy are intertwined with a wide range of social stigma and serve to reflect, legitimate and rationalize continued racist, gendered and classed discourses and practices. For the most part hers has been a lone feminist and critical voice in the South African field of “teenage pregnancy”, as she reflects in a recent paper, the feminist “engagement that there has been is a whisper in relation to the plethora of public health, medical and psychological writings on ‘adolescent pregnancy’” (Macleod, in press).